2000
DOI: 10.1093/emboj/19.15.4182
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic relocalization of phage φ29 DNA during replication and the role of the viral protein p16.7

Abstract: We have examined the localization of DNA replication of the Bacillus subtilis phage f29 by immuno¯uores-cence. To determine where phage replication was localized within infected cells, we examined the distribution of phage replication proteins and the sites of incorporation of nucleotide analogues into phage DNA. On initiation of replication, the phage DNA localized to a single focus within the cell, nearly always towards one end of the host cell nucleoid. At later stages of the infection cycle, phage replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
40
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 43 publications
4
40
0
Order By: Relevance
“…that the N-terminal region of the protein, constituting a transmembrane-spanning domain, is responsible for its membrane localization (2,10). Together with the results obtained in this work, we conclude that the native protein p16.7 is a membranelocalized, dimeric, ssDNA-binding protein.…”
Section: Protein P167a Has No Helix-destabilizing Activity and Has Nsupporting
confidence: 77%
See 4 more Smart Citations
“…that the N-terminal region of the protein, constituting a transmembrane-spanning domain, is responsible for its membrane localization (2,10). Together with the results obtained in this work, we conclude that the native protein p16.7 is a membranelocalized, dimeric, ssDNA-binding protein.…”
Section: Protein P167a Has No Helix-destabilizing Activity and Has Nsupporting
confidence: 77%
“…By immunofluorescence microscopy we have indeed confirmed that the majority of the replicated doublestranded 29 DNA molecules present at late infection times were no longer localized at the membrane. Rather, these molecules were found within the bulk of the host nucleoid (2). Finally, although the possibility, proposed by Ivarie and Pène (8), that the 29 gene 2 product, the DNA polymerase, could be directly involved in attachment of replicating 29 DNA to the membrane still holds, another perhaps more logic explanation can be considered.…”
Section: Protein P167a Has No Helix-destabilizing Activity and Has Nmentioning
confidence: 97%
See 3 more Smart Citations